Question and Answers Forum

All Questions      Topic List

Algebra Questions

Previous in All Question      Next in All Question      

Previous in Algebra      Next in Algebra      

Question Number 36019 by math1967 last updated on 27/May/18

If a+b+c=0 show that  ((a/(b−c))+(b/(c−a))+(c/(a−b)))(((b−c)/a)+((c−a)/b) +((a−b)/c))=9

Ifa+b+c=0showthat(abc+bca+cab)(bca+cab+abc)=9

Answered by ajfour last updated on 27/May/18

let b=pa  ,  c=qa  ⇒ a(1+p+q)=0          ...(i)     (shall be using this in many        steps that follow..)  l.h.s. = ((1/(p−q))+(p/(q−1))+(q/(1−p)))(((p−q)/1)+((q−1)/p)+((1−p)/q))     =1+(((q−1))/(p(p−q)))+(((1−p))/(q(p−q)))+        ((p(p−q))/(q−1))+1+((p(1−p))/(q(q−1)))+            ((q(p−q))/((1−p)))+((q(q−1))/(p(1−p)))+1     =3+((q^2 −q+p−p^2 )/(pq(p−q)))+((pq(p−q)+p(1−p))/(q(q−1)))+          ((pq(p−q)+q(q−1))/(p(1−p)))     =3+((1−p−q)/(pq))+((p[qp−q^2 +1−p])/(q(q−1)))+            ((q[p^2 −pq+q−1])/(p(1−p)))     =3+(2/(pq))+((p(p−q−1))/q)+((q(q−p−1))/p)     =3+((2+p^2 (p−q−1)+q^2 (q−p−1))/(pq))     =3+((2+p^3 +q^3 −pq(p+q)−(p^2 +q^2 ))/(pq))    =3+((2−(p^2 +q^2 −pq)+pq−1+2pq)/(pq))    =3+((2−1+2pq+pq+pq−1+2pq)/(pq))    = 3+6 = 9 .

letb=pa,c=qaa(1+p+q)=0...(i)(shallbeusingthisinmanystepsthatfollow..)l.h.s.=(1pq+pq1+q1p)(pq1+q1p+1pq)=1+(q1)p(pq)+(1p)q(pq)+p(pq)q1+1+p(1p)q(q1)+q(pq)(1p)+q(q1)p(1p)+1=3+q2q+pp2pq(pq)+pq(pq)+p(1p)q(q1)+pq(pq)+q(q1)p(1p)=3+1pqpq+p[qpq2+1p]q(q1)+q[p2pq+q1]p(1p)=3+2pq+p(pq1)q+q(qp1)p=3+2+p2(pq1)+q2(qp1)pq=3+2+p3+q3pq(p+q)(p2+q2)pq=3+2(p2+q2pq)+pq1+2pqpq=3+21+2pq+pq+pq1+2pqpq=3+6=9.

Commented by tanmay.chaudhury50@gmail.com last updated on 27/May/18

praisworthy...

praisworthy...

Answered by ajfour last updated on 27/May/18

l.h.s. = 3+Σ((a/(b−c)))[(((c−a)/b))+(((a−b)/c))]       =3+Σ((a/(b−c)))(((c^2 −ac+ab−b^2 )/(bc)))       =3+Σ((a^2 /(abc)))(a−b−c)       =3+Σ((a^2 /(abc)))(2a)     ∵ (−b−c=a)       =3+2Σ(a^3 /(abc))  and as  Σa^3 =3abc  if  Σa=0, so    l.h.s.  =3+2(((3abc)/(abc)))= 9 .

l.h.s.=3+Σ(abc)[(cab)+(abc)]=3+Σ(abc)(c2ac+abb2bc)=3+Σ(a2abc)(abc)=3+Σ(a2abc)(2a)(bc=a)=3+2Σa3abcandasΣa3=3abcifΣa=0,sol.h.s.=3+2(3abcabc)=9.

Answered by tanmay.chaudhury50@gmail.com last updated on 28/May/18

zLHS  3+(a/(b−c))×(((c−a)/b)+((a−b)/c))+(b/(c−a))×(((b−c)/a)+((a−b)/c))+  (c/(a−b))×(((b−c)/a)+((c−a)/b))  let us calculate   (a/(b−c))×(((c−a)/b)+((a−b)/c))  (a/(b−c))×(((c^2 −ac+ab−b^2 )/(bc)))  =(a/(b−c))×{((a(b−c)−(b^2 −c^2 ))/(bc))}  =(a/(b−c))×{(((b−c)(a−b−c))/(bc))}  =(a/(bc))×(a−b−c)  =(a/(bc))×2a   since a+b+c=0   so (−b−c)=a  =2(a^3 /(abc))  other two also give ((2b^3 )/(abc)) and ((2c^3 )/(abc))  so  3+((2a^3 )/(abc))+((2b^3 )/(abc))+((2c^3 )/(abc))  3+2(((a^3 +b^3 +c^3 )/(abc)))  3+2(((3abc)/(abc)))     =3+6  =9  if a+b+c=0  a^3 +b^3 +c^3 =3abc

zLHS3+abc×(cab+abc)+bca×(bca+abc)+cab×(bca+cab)letuscalculateabc×(cab+abc)abc×(c2ac+abb2bc)=abc×{a(bc)(b2c2)bc}=abc×{(bc)(abc)bc}=abc×(abc)=abc×2asincea+b+c=0so(bc)=a=2a3abcothertwoalsogive2b3abcand2c3abcso3+2a3abc+2b3abc+2c3abc3+2(a3+b3+c3abc)3+2(3abcabc)=3+6=9ifa+b+c=0a3+b3+c3=3abc

Terms of Service

Privacy Policy

Contact: info@tinkutara.com